Distal Radius Volar Rim Fracture Fixation Using DePuy-Synthes Volar Rim Plate - Kachooei, Amir Reza (J Wrist Surg, 2016)
Background To assess the results of distal radius fractures with the involvement of the volar rim fixed with the DePuy-Synthes Volar Rim Plate. Case Description We searched for the patients with volar rim fracture and/or volar rim fractures as part of a complex fracture fixed with a volar rim plate. Ten patients met the inclusion criteria: three patients with type 23B3, six patients with type 23C, and one patient with very distal type 23A. The mean follow-up was 14 months (range: 2–26). Fractures healed in all patients. Of the three patients with isolated volar rim fractures (type 23B3), two patients had no detectable deficits in motion. These patients had an average Gartland and Werley score of 9 (range: 2–14). Of the other seven patients (six with type 23C and one with type 23A fracture), three patients healed with full range of motion and four had some deficits in range of motion. Two patients had excellent results, three had good results, and two had fair results using the Gartland and Werley categorical rating. One patient healed with a shortened radius and ulnar impingement requiring a second surgery for ulnar head resection arthroplasty. Literature Review Results after nonoperative treatment of volar rim fractures are not satisfactory and often require subsequent corrective osteotomy. Satisfactory outcomes are achieved when the fragments are well reduced and secured regardless of the device type. Clinical Relevance Volar rim plates give an adequate buttress of the volar radius distal to volar projection of the lunate facet and do not interfere with wrist mobility. Furthermore, the dorsal fragments can be fixed securely through the volar approach eliminating the need for a secondary posterior incision. However, patients should be informed of the potential problems and the need to remove the plate if symptoms develop.